The Impact on Outcome by Adding Bevacizumab to Standard Induction Chemotherapy Prior to Mesothelioma Surgery: A Retrospective Single Center Analysis - Lauk, Olivia; Bruestle, Karina; Neuer, Thomas; Battilana, Bianca; Nguyen, Thi Dan Linh; Frauenfelder, Thomas; Stahel, Rolf; Weder, Walter; Curioni-Fontecedro, Alessandra; Opitz, Isabelle (Frontiers in Oncology, 2020)
Objectives: Adding bevacizumab, an anti-Vascular Endothelial Growth Factor (VEGF), to platinum-based chemotherapy/pemetrexed in 1st line treatment of advanced malignant pleural mesothelioma (MPM), significantly improved overall survival. However, increased high grade bleeding after operation was reported in patients with colorectal cancer who previously received bevacizumab. In the present analysis, we assessed for the first time the impact of adding bevacizumab to induction chemotherapy prior to surgery for mesothelioma patients. Methods: 227 MPM patients, intended to be treated with induction chemotherapy followed by surgery at the University Hospital of Zurich between 2002 and December 2018, were included in the present analysis. After propensity score matching for gender, histology and age (1:3 ratio), data from 88 patients were analyzed. 66 patients underwent induction chemotherapy (with cis-/carboplatin and pemetrexed: control group) alone and 22 patients underwent induction chemotherapy with the addition of bevacizumab (bevacizumab group) prior macroscopic complete resection (MCR). Perioperative and long-term outcome variables were analyzed. Results: Patients undergoing combination treatment with bevacizumab had a significantly better response than with chemotherapy alone as assessed by modified RECIST (p=0.046). Intraoperative complications in the bevacizumab group (one patient), or in the control group (three patients) were not related to intraoperative bleeding. Postoperative transfusion of blood products occurred in a larger amount in the control group than in the bevacizumab group (p=0.047). Overall survival was not statistically different between both groups. Conclusion: These initial data demonstrate that MCR can be performed safely after induction chemotherapy and bevacizumab without increased intra- and postoperative bleeding complications. Response rates were significantly improved by the addition of bevacizumab.